Sound, Place & Multiplace - Roddy, Stephen (My University, 2016)
While technology, particularly mobile and smart technology, can be viewed as furthering the eradication of real and “authentic” place; the argument can also be made that these same technologies, can also be instrumental in their recovery. Both alienator and facilitator, the impermeable membrane of the mobile screen and the headphone cuts us off from our surroundings while simultaneously providing us with a means of connecting and understanding through the private and intimate barrier they create. Such devices afford us a means to re-contextualise and redefine our experience and interaction within urban space. As technology becomes more advanced and widespread, it opens the possibility for new modes of artistic engagement and presentation within urban environments. Presenting artists and technologists, a constellation of possibilities to control and re-write our experience of the city and the everyday.
rish Sound Science and Technology Association Conference
Keywords: Creative Arts Practice; Creative Technologies; Smart & Sustainable Planet